Systematic classification of confocal laser endomicroscopy for the diagnosis of oral cavity carcinoma - Sievert, Matti; Oetter, Nicolai; Mantsopoulos, Konstantinos; Gostian, Antoniu-Oreste; Müller, Sarina Katrin; Koch, Michael; Balk, Matthias; Thimsen, Vivian; Stelzle, Florian; Eckstein, Markus; Iro, Heinrich; Goncalves, Miguel (Oral Oncology, 2022)
Introduction: Confocal laser endomicroscopy (CLE) is an optical imaging technique that allows in vivo microscope-like images of the upper aerodigestive tract's mucosa in 1000-fold magnification. The assessment of morphological tissue characteristics for the correct differentiation between healthy and malignoma suspected mucosa requires strict evaluation criteria. This study aims to validate a score for oral cavity squamous cell carcinoma (OCSCC) diagnostic. Methods: We performed CLE and examined a total of twelve patients. All 95 sequences (778 s, 6224 images) originate from the area of the primary tumor 260 s, 2080 images) and unsuspicious mucosa of the oral cavity (518 s, 4144 images). Specimen were taken at corresponding locations and analyzed histologically in H&E staining as a reference standard. A total of eight examiners (four experienced and four inexperienced) evaluated the sequences based on a scoring system. The primary endpoints are sensitivity, specificity, and accuracy. Secondary endpoints are inter-rater reliability and receiver operator characteristics. Results: Healthy mucosa showed epithelium with uniform size and shape with distinct cytoplasmic membranes and regular vessel architecture. CLE of malignant cells demonstrated a disorganized arrangement of variable cellular morphology. We calculated an accuracy, sensitivity, specificity, PPV, and NPV of 88.7 %, 90.1 %, 87.4 %, 87.5 %, and 90.0 %, respectively, with inter-rater reliability and κ-value of 0.775, and an area under the curve of 0.935. Conclusions: The results confirm that this scoring system is applicable in the oral cavity mucosa to classify benign and malignant tissue.
CRIS-Team Scopus Importer:2022-08-12
Keywords: Carcinoma; Squamous cell/diagnosis; Confocal laser endomicroscopy; Early detection of cancer*; Endoscopy; Fluorescence; Fluorescent dyes; Head and neck cancer; Head and neck neoplasms/diagnosis; Head and neck neoplasms/pathology*; Humans; Lasers; Margins of excision; Microscopy; Confocal/methods*; Mouth neoplasms*/diagnosis; Optical biopsy; Oral cavity squamous cell carcinoma; Safe surgical margins